Dragon in the mirror : China's image makeover? - Horta, Loro (2021)
In a recent address to senior party officials, Xi Jinping said it was important for China to create a new image. He instructed the party’s propaganda arm “to create a credible, lovable and respectable image of China”. Beijing seems to have realised that it has a serious image problem.